E-Services in Sudan During the Covid-19 Pandemic as a Model: a Case Study of University of Bahri-Sudan - Adil Hassan Ibrahim; Dyah Mutiarin; Eko Priyo Purnomo (Journal of Governance and Public Policy, 2021)
The study aims to explore the barriers of online learning in Sudan. The achievement of the research purpose requires an approach which is not only describes the relations between variables, but also the experience of the stakeholders, therefore, the study adopted mixed mothed approach. To collect data, the study used two sources; secondary, and primary data sources.  The secondary sources included peer-review international journals from recognized publishers, books, newspapers and reports. The primary sources included questionnaires and interviews. 132 participants were surveyed. Two professors were interviewed. SPSS was used to analyze the data. The findings indicate that there are five unique barriers to e-learning adoption in Sudan including; poor network infrastructure, lack of bandwidth in rural areas, electricity outages, lack of electricity in rural areas, and stakeholder’s deficiency of e-skills. Furthermore, the study showed that some professors are old, and they resist the adoption of e-learning. Likewise, the study found that 67% of respondents were not able to access the internet in their areas during Covid19 lockdown, 25% of respondents do not possess computers, 35% of respondents did not receive training for gaining E-skills, and 74% of respondents prefer learning in classrooms. The study concluded that, E-learning to be adopted in Sudan, several steps can be taken such as e-skills intensive training for stakeholders, support of stakeholders, electricity and internet networks connection to whole parts of Sudan, poverty combat, and stimulation of students to accept e-learning.